Characterization of Medication Errors in a Medical Intensive Care Unit of a University Teaching Hospital in South Korea. Issue 1 (28th July 2021) - Yoon, Jimin; Yug, Ji Seob; Ki, Dae Yun; Yoon, Ji-Eun; Kang, Sung Wook; Chung, Eun Kyoung
Abstract : Objectives: The objective of this study was to characterize the current status of medication errors (MEs) throughout the medication therapy process from prescribing to use and monitoring in a medical intensive care unit (MICU) in Korea. Methods: Four trained research pharmacists collected data through retrospectively reviewing electronic medical records for adults hospitalized in the MICU in 2017. The occurrence of MEs was determined through interprofessional team discussion led by an academic faculty pharmacist and a medical intensivist based on the medication administration records (MARs). The type of MEs and the consequent ME-related outcome severity were categorized according to the Pharmaceutical Care Network Europe and the National Coordinating Council for Medication Error Reporting and Prevention, respectively. Results: Overall, electronic medical records for 293 patients with 78, 761 MARs were reviewed in this study. At least one type of ME occurred in 271 patients (92.5%) in association with 16, 203 MARs (21%), primarily caused by inappropriate dose (35.5%), drug (27.8%), and treatment duration (25.1%). Clinically significant harmful events occurred in 24 patients (8%), including life-threatening (n = 5) and death (n = 2) cases. The 2 patients died of enoxaparin-induced fatal hemorrhage and neutropenia associated with ganciclovir and cefepime. Antibiotics were the most common culprit medications leading to clinically significant harmful events. Conclusions: In conclusion, MEs are prevalent in the MICU in Korea, most commonly prescribing errors. Although mostly benign, harmful events including deaths may occur due to MEs, mainly associated with antibiotics. Systematic strategies to minimize these potentially fatal MEs are urgently needed.